Diagnosis of Pure Ulnar Sensory Neuropathy Around the Hypothenar Area Using Orthodromic Inching Sensory Nerve Conduction Study: A Case Report - Min Je Kim; Jong Woo Kang; Goo Young Kim; Seong Gyu Lim; Ki Hoon Kim; Byung Kyu Park; Dong Hwee Kim (Annals of Rehabilitation Medicine, 2018)
Ulnar neuropathy at the wrist is an uncommon disease and pure ulnar sensory neuropathy at the wrist is even rarer. It is difficult to diagnose pure ulnar sensory neuropathy at the wrist by conventional methods. We report a case of pure ulnar sensory neuropathy at the hypothenar area. The lesion was localized between 3 cm and 5 cm distal to pisiform using orthodromic inching test of ulnar sensory nerve to stimulate at three points around the hypothenar area. Ultrasonographic examination confirmed compression of superficial sensory branch of the ulnar nerve. Further, surgical exploration reconfirmed compression of the ulnar nerve. This case report demonstrates the utility of orthodromic ulnar sensory inching test.